Optimization of cultural parameters for lipase production by indigenous stenotrophomonas sp. And pseudomonas aeruginosa isolated from lipid-rich environments (Bangladesh Journal of Botany, 2023)
The present study aims to identify prospective lipase-producing bacteria and optimize different culture parameters to produce maximum lipase. A total of 37 lipase-positive bacteria were isolated from lipid-rich environments. Among them, strains S1N-2 and S10P-1 were found to have potential and were molecularly identified as Stenotrophomonas species ICMM10 and Pseudomonas aeruginosa BA7823, respectively. For maximum lipase production, the optimum pH was 7 and the temperature was 37ºC. Using these conditions, the isolates were grown on media with additional carbon and nitrogen sources along with different inoculum concentrations. The maximum amount of lipase produced by Stenotrophomonas sp. ICMM10 was 136.47 ± 1.63 U/ml, which is 5-fold higher than before. Pseudomonas aeruginosa BA7823 produced a maximum lipase of 96.33 ± 0.21 U/ml, which was about 9-fold higher than before. These results would provide useful information about lipase production by indigenous isolates, which may be employed as a potential bacterial lipase source of biotechnological interest.Bangladesh J. Bot. 52(4): 979-988, 2023 (December)